Ampicillin treatment in persister cell studies may cause non-physiological artifacts - Michel Fasnacht; Hena Comic; Isabella Moll (Microbial Cell)
Persister cells are a clinically relevant sub-population of an isogenic bacterial culture that is tolerant to bactericidal antibiotics. With the aim to investigate the ribosomal protein content of persister cells, we employed the bacteriolytic properties of ampicillin to separate persister from sensitive cells. Thereby, we observed processing of several ribosomal proteins. Promisingly, we detected a variant of the large subunit protein uL2 that lacks the last 59 amino acids from its C-terminus (tL2) and which previously has been described as an inhibitor of DNA replication in vitro. Considering the increasing number of moonlighting functions described for ribosomal proteins, we investigated a potential regulatory role of tL2 in persister cells after ampicillin treatment. In contrast to our assumption, our findings show that the generation of tL2 after ampicillin treatment must be attributed to proteolysis upon cell lysis. Ultimately, no tL2 was detected intracellularly of purified persister cells isolated by an improved protocol employing proteinase K treatment. We therefore exclude the possibility of tL2 regulating DNA replication in ampicillin tolerant E. coli cells. Nevertheless, this study clearly highlights the necessity of further purification steps in addition to ampicillin treatment for the study of persister cells and invites for the careful re-examination of previously published results.